PREPARASI, SINTESIS Dan KARAKTERISASI MATERIAL CaMnO3 [Preparation, Synthesis and Characterization of CaMnO3 Material] - Hasbi, M. Yunan; Yudanto, Sigit Dwi (Jurnal Metalurgi, 2015)
CaMnO is metal oxide compound with wide potential applications i.e thermoelectric. Synthesis of CaMnO, using carbonat groups material has been succesfully carried out through solid state reaction method. It is started by mixing of both CaCO, and MnCo, raw materials at a stoichimometri composition and followed by grinding. calcinating, pelletizing and sintering at various temperatures of 1100 °C, 1200 °C and 1250 °C. X-Ray diffraction results for all specimens show similar pattern at each temperature condition, namely the formation of single phase CaMnO,. Crystal lattice from refinement with Rietviled method that has been identified in orthorombic crystal system and Pnma space group was a = ~5,26 A; b = ~7,44 A; dan c = ~5,27 A. Microstructure of CaMnO, phase shows that increasing temperature will increase grain density and reduce grain space.